GROWTH PRFORMANCE IN NIGERIA’S FISCAL SYSTEM - Philip, Abachi Terhemen (European Scientific Journal, ESJ, 2013)
The study examines the performance of economic growth in Nigeria in the country’s fiscal system. Four sectors of the economy and two economic indicators are used in analyzing the growth performance from 1960 to 2010. Using tables and secondary data from the Central Bank of Nigeria from 1960 to 2010, the analysis was done and the results indicated that in the pre 1966 period, agricultural sector dominated and contributed more to GDP, but its contribution continues to decline after 1966. The industrial sector, particularly the oil sub-sector dominated the economy from 1970 and its share contributions have been on the increase. Other sectors’ contributions are positive but not so pronounced within the period. Again, both exchange and inflation rates, as observed in the study, are unpredictable and can not ensure meaningful planning. We therefore recommend the effective development of other sectors of the economy to avoid the danger of complete dependence on the oil sector and measures to stabilize exchange and inflation rates should be undertaken in Nigeria.